Spirituality-based narrative counseling model to reduce self-injurious behavior in Islamic boarding school students - Sari, Dita Kurnia; Abidin, Muhammad Nasrullah bin Zainal (Journal of Professional Teacher Education, 2023)
The aim of this research is to develop a spirituality-based narrative counseling model to reduce self-injurious behavior. The basis for developing this counseling model is a postmodern approach by adapting the spiritual values inherent in Islamic boarding school students. The development of a spirituality-based narrative counseling model in this research is based on the research and development model of Borg & Gall (1983) and only focuses on three main stages, including: (1) identifying students' self-injurious behavior profiles; (2) draft a hypothetical spirituality-based narrative counseling model to reduce students' self-injurious behavior; and (3) conducting an acceptability test of the model developed through one expert in the field of guidance and counseling and one Islamic boarding school counselor. The data analysis technique used in this research is quantitative and descriptive analysis. The results of the study showed that the level of self-harming behavior of Islamic boarding school students in Taman District, Sidoarjo Regency was 14.80% indicating a high level of self-injuring behavior, 59.54% a moderate level of self-injuring behavior and 30.61% a low level of self-injuring behavior. Based on the results of the analysis, a spirituality-based narrative counseling model which includes six stages is acceptable (feasible) for use by counselors in Islamic boarding schools. The results of this research can be followed up by future researchers by testing the effectiveness of spirituality-based narrative counseling to reduce self-injurious behavior in Islamic boarding school students